1995
DOI: 10.1007/bf00017682
|View full text |Cite
|
Sign up to set email alerts
|

Some effect of sodium application on the yield and chemical composition of pasture grown under differing conditions of potassium and moisture supply

Abstract: The effects of Na fertiliser (supplied as an NPK-Na compound) on herbage yield and composition were examined at two different sites to see if pasture responses to Na were affected by differences in K and moisture availability. At one site, pasture was grown under conditions of moisture stress and limited K availability, whereas at the other site the pasture was grown under comparatively non-stress conditions.The results were interesting in that Na fertilisation appeared to be detrimental to pasture yield and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 26 publications
(25 reference statements)
4
19
0
1
Order By: Relevance
“…For example, K uptake and efficiency from either soil or K applications often depended on the rate of N used (Ebelhar, Kamprath, & Moll, 1987). Likewise, K was known to have a key role in N uptake and translocation (Cushnahan, Bailey, & Gordon, 1995). Therefore, some nutrients (such as N and K) need to be kept in the specific nutrient ratios to develop the plants.…”
Section: Resultsmentioning
confidence: 99%
“…For example, K uptake and efficiency from either soil or K applications often depended on the rate of N used (Ebelhar, Kamprath, & Moll, 1987). Likewise, K was known to have a key role in N uptake and translocation (Cushnahan, Bailey, & Gordon, 1995). Therefore, some nutrients (such as N and K) need to be kept in the specific nutrient ratios to develop the plants.…”
Section: Resultsmentioning
confidence: 99%
“…Nitrogen and S are vital constituents of sulphur-containing amino acids and need to be present in quite specific proportions if the requisite proteins and proteincontaining structures are to be synthesized by plants (Marschner 1995). Equally, K is known to have a key role in N uptake and translocation (Minotti et al 1968;Cushnahan et al 1995), and therefore both N and K need to be present in quite specific proportions if N accumulation and subsequent assimilation into proteins is to take place at optimal rates. There is perhaps less obvious physiological rationale for maintaining specific P/N, K/P, S/P and K/S ratios in leaf tissue, and this is probably why at least three of these ratios (P/N, K/P and K/S) had CV's greater than 30%.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have indicated that in situations where K is moderately deficient, plant uptake of N, and shoot dry matter (DM) yield, may be enhanced by the application of Na containing fertilisers (Bailey, 1993;Phillips, 1991, 1993a;Cushnahan and Bailey, 1994;McNaught and Karlovsky, 1964;Smith et al, 1980), whereas in situations of K abundance, Na K + would have been made available to drive the NO − 3 transport mechanism, and hence NO − 3 would either have accumulated in roots hindering further N uptake by feed back regulation (Haynes, 1986), or else would be reduced in root tissue at exorbitantly high C costs (i.e., 2.17 moles of C per mole of NO − 3 reduced) and thus at the expense of subsequent NO − 3 uptake (Cushnahan et al, 1995;Raven, 1985). In contrast, in K sufficient situations, they found that the application of Na had little or no effect on DM production or N recovery by grassland swards (Bailey, 1993;Bailey and Cushnahan, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…in concentrated complex fertiliser (CCF) form. Cushnahan et al (1995) proposed a physiological framework to explain the differential effects of Nacontaining CCF's on NO − 3 uptake under K-deficient and K-sufficient conditions. Based on the results of previous studies they suggested that the initial rate of NO − 3 absorption by plant roots is directly proportional to the supply of metallic cations (K + , Na + , Mg 2+ , Ca 2+ ) in the soil solution (Minotti et al, 1968(Minotti et al, , 1969.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation